Citizens Must Go! An Essay Review of Corporatizing Rural Education: Neoliberal Globalization and Reaction in the United States by J. A. Cervone - Craig B. Howley; James Clifton; Aimee Howley (Journal of Research in Rural Education, 2018)
Jason Cervone's Corporatizing Rural Education off ers a critical account of contemporary corporate power over rural schooling, writ very large. Rural education especially needs these broad and critical accounts to remind educators and rural community members whose world this is (ours) and who should own it (we should): as in we, the people. Powerful members of the corporatizing nation state and world, needless to say, think and act otherwise.